PERAN BABINSA DALAM KEGIATAN DETEKSI DINI GUNA PENCEGAHAN AKSI TERORISME (RELEVANSI DI WILAYAH KODIM 0618/BS KOTA BANDUNG) - Simanjuntak, Komarudin (Jurnal Ketahanan Nasional, 2015)
This study aimed to determined the role of non-commissioned officer in the early detection activities, constraints Babinsa role in the early detection activities and formulated efforts to optimized Babinsa role in the early detection of activities for the prevention of terrorism. Methods This study used a qualitative approach, with the data collection technique: First, theoretical orientation; collecting data with three stages, orientation, exploratory data collection, and research focus; Second, in-depth interviews and comprehensive; Third, the observation participation; and Fourth, documentation. In this study would be taken groups / people associated with problems Babinsa role in the early detection of activities to discovered problems in the field of the structural officials in institutional organization. The results were expected to knew about the current objective conditions Babinsa role in the early detection activities at the level of understanding and awareness as well as its ability to helped prevention and control of terrorism in the region, as well as being able to identifi ed the success factors in the activities of early detection as well as constraints in implementing the role seen on environmental aspects of security level. Then, about commitment and public awareness participating in the prevention and control of terrorism, by reviewing how institutional Babinsa accompanied by cooperation between the relevant authorities in handling the increasing role of Babinsa. Thus, could find the policy, strategy and efforts were enhanced through regular coaching related apparatus and increase the capabilities Babinsa role in the early detection activities, as well as the handling in helping the integration of prevention and control of terrorism.Keywords: Role of Babinsa, Early Detection, Terrorism